2018
DOI: 10.1007/s00432-018-2756-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prognostic factors of more/equal to10 years of survival for liver cancer patients after liver transplantation

Abstract: ObjectiveTo investigate prognostic factors of  more than 10 years of survival for liver cancer patients after liver transplantation.MethodsFrom May 2000 to May 2007, a total of 134 liver cancer patients who underwent liver transplantation in the Department of Hepatobiliary Surgery, Peking University People’s Hospital, were continuously and retrospectively enrolled. The patients included 120 males and 14 females. There were 124 cases (92.5%) of primary hepatocellular carcinoma, 9 cases (6.7%) of cholangiocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Several studies have focused on the 10-year survivors of HCC, and these studies only focus on one treatment [4][5][6][7]. Liver transplantation is the optimal treatment option for early HCC, but it was limited by lack of donor organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on the 10-year survivors of HCC, and these studies only focus on one treatment [4][5][6][7]. Liver transplantation is the optimal treatment option for early HCC, but it was limited by lack of donor organs.…”
Section: Introductionmentioning
confidence: 99%
“…Liver transplantation is the optimal treatment option for early HCC, but it was limited by lack of donor organs. One study reported that the actual 10-year survival rate for HCC patients who had liver transplantation was 41.1% [ 6 ]. For patients who underwent resection, the actual 10-year survival rate of patients was about 7.2%, whereas the actuarial survival quoted from the same studies was 26.8% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liver transplantation is applied for selected patients with early stage HCC with favorable tumor biology. 1 , 2 Therefore, liver resection plays an important role in the treatment of HCC patients. However, many HCC patients are not candidates for liver resection at the time of diagnosis due to poor liver functions, multifocal tumor, small remnant liver volume or proximity to major hepatic vasculatures.…”
Section: Introductionmentioning
confidence: 99%
“…The treatments for early-stage patients include hepatectomy, transplantation and radiofrequency ablation [4–7] . However, most patients are diagnosed at an advanced stage of liver cancer, thus the curative rates of the above treatments are relatively low [8] . Therapies for patients at more advanced stage contain trans-arterial chemoembolization and chemotherapy [7] .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] However, most patients are diagnosed at an advanced stage of liver cancer, thus the curative rates of the above treatments are relatively low. [8] Therapies for patients at more advanced stage contain transarterial chemoembolization and chemotherapy. [7] However, the chemoresistance of liver cancer is considerably high and this may lead to a low overall response rate.…”
Section: Introductionmentioning
confidence: 99%